Optimal Placement of Distributed Generation Units in Power Distribution Networks Using Particle Swarm Optimization - Suwi, Owdean M.; Justo, Jackson J.; Mighanda, Manyahi J. (Tanzania Journal of Engineering and Technology, 2025)
Power losses and voltage drops in distribution networks are critical issues in power system operation, reducing efficiency, reliability, and overall quality of the power supply to customers. Additionally, the rising electricity demand, deregulation of energy markets, and congestion in transmission networks have further contributed to the declining performance of the grid. To address these challenges, integrating distributed generation units (DGUs) into electric distribution systems has gained significant attention. Furthermore, the integration of DGUs into conventional fossil fuel-based power plants is becoming necessary to reduce greenhouse gas emissions. However, proper placement and sizing of DGUs are crucial for achieving optimal benefits. Inappropriate placement and sizing can lead to increased losses and degraded system performance, whereas optimal placement can enhance voltage stability and minimize power losses, thereby improving overall system performance. This study presents a particle swarm optimization (PSO) technique for determining the optimal placement and sizing of DGUs in power distribution networks. The proposed PSO approach considers voltage and power constraints to ensure operational requirements are met. The methodology is validated using IEEE 33-bus system simulations under three different scenarios: a network without DGUs, a network with one DGU, and a network with two DGUs. Simulation results demonstrate that optimal DGU placement significantly reduces power losses, minimizes voltage drops, and enhances system performance compared to a network without DGUs.